2021
DOI: 10.3390/molecules26175259
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Quaternary Ammonium in Reducing Microbial Load on Eggs

Abstract: Table eggs are an affordable yet nutritious protein source for humans. Unfortunately, eggs are a vector for bacteria that could cause foodborne illness. This study aimed to investigate the effectiveness of a quaternary ammonium compound (quat) sanitizer against aerobic mesophilic bacteria, yeast, and mold load on the eggshell surface of free-range and commercial farms and the post-treatment effect on microbial load during storage. Total aerobic mesophilic bacteria, yeast, and molds were enumerated using plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The U.S. Department of Health and Human Services, Food and Drug Administration Center for Food Safety and Applied Nutrition recommends that sanitizers used in egg washing must contribute to a minimum of 5 log reduction of Salmonella Enteritidis ( Hunt et al, 2023 ). Chlorine-based sanitizers like QA are widely used in commercial egg washing ( Bialka et al, 2004 ; Cao et al, 2009 ; Chan et al, 2021 ). The results of this study imply that PAW could potentially be used as an alternate sanitizer to QA, because our analysis showed that PAW, like QA, resulted in more than 5 log reduction in Klebsiella michiganensis population.…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Department of Health and Human Services, Food and Drug Administration Center for Food Safety and Applied Nutrition recommends that sanitizers used in egg washing must contribute to a minimum of 5 log reduction of Salmonella Enteritidis ( Hunt et al, 2023 ). Chlorine-based sanitizers like QA are widely used in commercial egg washing ( Bialka et al, 2004 ; Cao et al, 2009 ; Chan et al, 2021 ). The results of this study imply that PAW could potentially be used as an alternate sanitizer to QA, because our analysis showed that PAW, like QA, resulted in more than 5 log reduction in Klebsiella michiganensis population.…”
Section: Discussionmentioning
confidence: 99%